Small airway dysfunction measured by impulse oscillometry is associated with exacerbations and poor symptom control in patients with asthma treated in a tertiary hospital subspecialist airways disease clinic - Beinart, Dylan; Goh, Emily S. Y.; Boardman, Glen; Chung, Li Ping (Frontiers in Allergy, 2024)
IntroductionSmall airways dysfunction contributes to asthma pathophysiology and clinical outcomes including exacerbations and asthma control. Respiratory oscillometry is a simple, non-invasive and effort independent lung function test that provides vital information about small airway function. However, interpretation and clinical utility of respiratory oscillometry has been in part limited by lack of agreed parameters and the respective cutoffs. The aim of this study was to determine the prevalence of small airways dysfunction based on published impulse oscillometry (IOS) definition in patients with asthma referred to a tertiary asthma clinic and the extent to which it correlates with asthma clinical outcomes.MethodsWe retrospectively reviewed the medical records of all patients with asthma managed in the severe asthma clinic between January 2019 and December 2022 who underwent routine lung function tests with oscillometry and spirometry. Small airways dysfunction was determined from various published IOS parameter cutoffs, and the data were analysed to determine correlations between IOS parameters and asthma outcomes.ResultsAmongst the 148 patients, the prevalence of small airways dysfunction ranged from 53% to 78% depending on the defining oscillometry parameter. All oscillometry parameters correlated with the severity of airflow obstruction (FEV1% predicted, p < 0.001). Several oscillometry parameters correlated with asthma symptom burden, the strongest correlation was seen for frequency dependent resistance (R5–R20) with scores of Asthma Control Questionnaire (ACQ6) (Spearman's rank coefficient 0.213, p = 0.028) and Asthma Control Test (ACT) (Spearman's rank coefficient −0.248, p = 0.012). R5–R20 was predictive of poor asthma control defined by ACQ6 >1.5 (OR 2.97, p = 0.022) or ACT <20 (OR 2.44, p = 0.055). Small airways dysfunction defined by R5–R20 and area under the reactance curve (AX) also significantly increases asthma exacerbation risk (OR 2.60, p = 0.02 and OR 2.31, p = 0.03 respectively).ConclusionRespiratory oscillometry is a sensitive measure of small airways dysfunction that should complement spirometry in the routine assessment of asthma. Small airways dysfunction is highly prevalent in patients with asthma referred to a tertiary asthma clinic. R5–R20 was the metric most predictive in identifying patients at risk of asthma exacerbations and poor asthma control.